Combination of Tumor Mutational Burden and Specific Gene Mutations Stratifies Outcome to Immunotherapy Across Recurrent and Metastatic Head and Neck Squamous Cell Carcinoma - Peng, Ying-Peng; Wang, Rong; Liu, Qiao-Dan; Xu, Xi-Wei; Wei, Wei; Huang, Xiao-Tao; Peng, Xiao-Mou; Liu, Zhi-Gang (Frontiers in Genetics, 2021)
Purpose: To investigate the prognostic significance of tumor mutational burden (TMB) combined with specific prognosis-related gene mutations in immunotherapy for recurrent and metastatic head and neck squamous cell carcinoma (r/m HNSCC). Methods: One hundred thirty-two r/m HNSCC patients from the Morris and Allen cohorts had undergone immunotherapy. We constructed the immunotherapy-related gene prognostic index TP-PR combining TMB and PIK3CA, TP53, or ROS1 mutation. And we analyzed the differences in overall survival (OS) and immune cell infiltration between samples in different groups. The association of each signature’s single-sample gene set enrichment analysis scores with TP-PR was tested using Spearman’s correlation test. Results: The median OS of the patients with high TMB (TMB ≥10 mut/Mb) who received immunotherapy for r/m HNSCC was 2.5 times as long as that of the patients with low TMB (25 vs. 10 months). More importantly, the high TP-PR (TP-PR >0) group had better median OS (25 vs. 8 months) than the low TP-PR (TP-PR ≤0) group. CD8+ T cells and activated memory CD4+ T cells in the tissues of the patients with high TP-PR were higher than those in the patients with low TP-PR. Results showed that TP-PR stratification had a higher area under the curve (AUC) value (0.77, 95% CI 0.86–0.68) compared with TMB stratification (0.56, 95% CI 0.68–0.44). The differential gene expression in the high and low TP-PR groups mainly influenced metabolism-related signaling pathways. Conclusion: TP-PR was an effective predictor of immunotherapy outcome for r/m HNSCC, which might be better than TMB alone. Patients with high TP-PR had a better survival benefit than had the patients with low TP-PR.